Historical development and future perspective of conservation agriculture practices in crop-pasture rotation systems in the Mediterranean region of South Africa - Swanepoel P.A.; Labuschagne J.; Hardy M.B. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
The Mediterranean region of South Africa is confined to the south-western parts of the country and is divided into two sub-regions: The Swartland and the southern Cape sub-regions, which receive ca. 80 and 60% of their rainfall in winter, respectively. The original vegetation is classified as lowland coastal renosterveld, which is a short, fire-prone, sclerophyllous shrubland. Renosterveld is associated with finetextured, low to moderately-fertile, shale-derived soils, with a low natural carrying capacity of 12 to 25 hectares per livestock unit. Ninety three per cent of the area has been transformed to crop and crop-pasture production systems with wheat and other small grains, canola, lupins, lucerne and medics used in various combinations in the rotation. The fodder component of these systems supports mostly sheep farming. The aim of this paper is to provide a synthesis of the challenges and opportunities related to issues involving soil conservation in the Mediterranean region of South Africa. This paper highlights the importance of research on soil quality and conservation agriculture, to ensure sustainability of crop and pasture production. The agricultural and ecological significance of soil tillage, crop rotation sequence, soil organic matter and soil microbial functionality will be discussed.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)